Pengaruh Relationship Marketing, Trust, Commitment, Citra, Dan Fasilitas Pada Customer Loyalty - Budhi Haryanto; Soemarjati T.J (Universitas Airlangga, 2009)
Objective of this study is to examine the influence of relationship marketing, customer trust, customer commitment, image and facility on customer loyalty. Sample size consists of 200 customers that have intention to loyal toward Hotel Pondok Indah Boyolali-Jawa Tengah. This sample was taken by purposive sampling technique. Validity and reliability testing were done to assurance the truth of data quality that was collected from survey. Analysis of variance (ANOVA) was chosen to elaborate the linkage among of these observed variables. The result indicates that customer loyalty significantly influence by trust, commitment, image, and facility. Insignificantly result and implication for further research are also discussed in this study.